The political style of conspiracy : Chase, Sumner, and Lincoln - Pfau, Michael William, 1971- (East Lansing : Michigan State University Press, 2005)
"This book analyzes the concept and reality of the "slave power" in the rhetorical discourse of the mid-nineteenth-century, in particular the speeches and writing of politicians Salmon P. Chase, Charles Sumner, and Abraham Lincoln. By examining their mainstream texts, Pfau reveals that, in addition to the "paranoid style" of conspiracy rhetoric that inhabits the margins of political life, Lincoln, Chase, and Sumner also engaged in a distinctive form of conspiracy rhetoric that is often found at the center of mainstream American society and politics."--Jacket.
Problems of interpretation : approaching conspiracy in text and discourse -- The slave power according to Salmon P. Chase : entering the mainstream of partisan rhetoric, 1845-1854 -- Charles Sumner's "crime against Kansas" : conspiracy rhetoric in the oratorical mold -- Lincoln, conspiracy rhetoric, and the "house divided" : assessing the judgment of history -- Lessons of the slave power conspiracy : conspiracy rhetoric at the center and fringe.
Includes bibliographical references (pages 231-243) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Chase, Salmon P. -- 1808-1873 -- Language; Sumner, Charles, -- 1811-1874 -- Language; Lincoln, Abraham, -- 1809-1865 -- Language; Chase, Salmon P. -- 1808-1873; Lincoln, Abraham, -- 1809-1865; Sumner, Charles, -- 1811-1874; Chase, Salmon P. -- 1808-1873 -- Language; Sumner, Charles, -- 1811-1874 -- Language; Lincoln, Abraham, -- 1809-1865 -- Language; United States -- Politics and government -- 1815-1861.; Slavery -- Political aspects -- United States -- History -- 19th century; Conspiracies -- United States -- History -- 19th century; Rhetoric -- Political aspects -- United States -- History -- 19th century; English language -- Discourse analysis; Political culture -- United States -- History -- 19th century; États-Unis -- Politique et gouvernement -- 1815-1861.; Discours politique -- États-Unis -- Histoire -- 19e siècle.; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; Conspiracies; English language -- Discourse analysis; Language and languages; Political culture; Politics and government; Rhetoric -- Political aspects; Slavery -- Political aspects; United States; Politische Sprache; Rhetorik; Verschwörung; USA; Slavery -- Political aspects -- United States -- History -- 19th century; Conspiracies -- United States -- History -- 19th century; Rhetoric -- Political aspects -- United States -- History -- 19th century; English language -- Discourse analysis; Political culture -- United States -- History -- 19th century; United States -- Politics and government -- 1815-1861.; Amerikanisches Englisch; 1800-1899; Geschichte 1815-1861; History